2007
DOI: 10.1590/s1676-24442007000300012
|View full text |Cite
|
Sign up to set email alerts
|

Association of manganese superoxide dismutase gene polymorphism (Ala-9Val) and breast cancer in males and females

Abstract: Introduction: One of the several metabolic pathways involved in breast carcinogenesis is the human polymorphism in the mitochondrial targeting sequence Ala-9Val of the manganese superoxide dismutase (MnSOD) gene, which has been previously associated with increased risk of breast cancer in females. Since there is no previous report on this polymorphism in male breast cancer, the objective of this study is to analyze MnSOD polymorphism in a population of males and females with breast cancer from the southernmost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Ginger was reported to suppress TPA-induced oxidative stress in human promyelocytic leukemia [29]. In some research works it have been proved that ginger compounds effectively inhibit superoxide production [30]. Several reports indicate that ginger suppresses lipid peroxidation and protects the levels of reduced glutathione [31].Ginger was reported to decrease age-related oxidative stress markers and was suggested to guard against ethanol-induced hepatotoxicity by suppressing oxidative consequences in rats treated with ethanol [32].…”
Section: Discussionmentioning
confidence: 99%
“…Ginger was reported to suppress TPA-induced oxidative stress in human promyelocytic leukemia [29]. In some research works it have been proved that ginger compounds effectively inhibit superoxide production [30]. Several reports indicate that ginger suppresses lipid peroxidation and protects the levels of reduced glutathione [31].Ginger was reported to decrease age-related oxidative stress markers and was suggested to guard against ethanol-induced hepatotoxicity by suppressing oxidative consequences in rats treated with ethanol [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Woodson et al [25] and Kang et al [26] found that the Ala allele was associated with an increased risk of PCa, whereas the Val allele was related with an increased risk of lung cancer [27] and of bladder cancer [28]. However, other studies showed different results, probably because of gene-gene, geneenvironmental, and physiological interactions associated with MnSOD polymorphism and cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…Manganese superoxide dismutase (MnSOD) is the most effective antioxidant enzyme in mitochondria and has an important role in protecting cells from reactive oxygen species (ROS)–induced oxidative damage . It has been suggested that MnSOD (Ala‐9Val) gene polymorphism may alter the secondary structure of the protein and affects transport of MnSOD enzyme into the mitochondria .…”
Section: Introductionmentioning
confidence: 99%
“…208 Por otra parte, la investigación también sugiere que el genotipo VV, que presenta una menor eficiencia de la enzima SOD2, está relacionado con la disfunción endotelial e indicadores bioquímicos asociados con el riesgo cardiometabólico, como es el caso de las LDL oxidadas, y también interactúa con la hipercolesterolemia aumentando la tasa de peroxidación de lípidos y disminuyendo los niveles de enzimas antioxidantes como la propia SOD. 209 Las investigaciones realizadas por el equipo de investigación relacionado con la ejecución del presente estudio han encontrado una asociación entre el genotipo/alelo y el cáncer de mama en mujeres y hombres 210,211 , el cáncer de próstata y la inmunosenescencia 212 , mientras que otros estudios, también llevados a cabo por nuestro equipo de investigación, han encontrado una asociación entre el genotipo VV/alelo V y altas concentraciones de LDL oxidado, especialmente en pacientes mayores con diabetes tipo II 213 e hipercolesterolemia 214 , y sorprendentemente con mayor agresividad tumoral en aumento (mayor probabilidad de afectación ganglionar en el cáncer de mama). 215 Con base a estos resultados se desplegaron también en las investigaciones in vitro mediante la construcción de líneas de linfocitos primarios y secundarios derivados de los individuos sanos (1) ¿Está la obesidad asociada a un estado inflamatorio de bajo grado?…”
Section: Genética De La Superóxido Dismutasa Dependiente De Manganesounclassified